Kepemimpinan di Era Digital: Strategi Memimpin Bisnis di Tengah Perubahan Teknologi Sistematic Literatur Review - Ahmad Azharuddin; Siti Mi'Danur Rahmah; Shela Dwi Widhya Sari; Siti Sri Wulandari; Yessy Artanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The digital era has changed the leadership paradigm, requiring leaders to integrate entrepreneurial skills with technological mastery. This study aims to analyze effective leadership strategies in the midst of digital transformation through a systematic literature review of recent studies (2015-2024). The findings show that entrepreneurial leadership-with characteristics such as strategic vision, adaptability, and risk-taking ability-is a crucial approach in dealing with technological disruption. Digital leaders not only need to leverage technologies such as AI and big data, but also build an organizational culture that supports innovation and collaboration. This research identifies gaps in the literature, especially in the context of SMEs, and offers practical recommendations in the form of digital competency development, data-driven approaches and controlled experiments. The results provide a holistic framework for leaders to spur digital transformation while maintaining organizational sustainability.